Isolation of Endophytic Salt-Tolerant Plant Growth-Promoting Rhizobacteria From Oryza sativa and Evaluation of Their Plant Growth-Promoting Traits Under Salinity Stress Condition - Jhuma, Tania Akter; Rafeya, Jannatul; Sultana, Shahnaz; Rahman, Mohammad Tariqur; Karim, Muhammad Manjurul (Frontiers in Sustainable Food Systems, 2021)
The application of plant growth-promoting rhizobacteria (PGPR) as vital components for plant growth promotion against biotic and abiotic stresses could be a promising strategy to improve crop production in areas vulnerable to increasing salinity. Here, we isolated Seventy-five endophytic bacteria from roots of healthy Oryza sativa grown in a saline environment of the southern coastal region of Bangladesh. The endophytes in a culture of 108 CFU/ml showed arrays of plant growth-promoting (PGP) activities: phytohormone (Indole acetic acid) production (1.20 - 60.13 µg/ ml), nutrient (phosphate) solubilization (0.02 - 1.81 µg/ml) and nitrogen fixation (70.24 - 198.70 µg/ml). Four genomically diverse groups were identified namely, Enterobacter, Achromobacter, Bacillus, and Stenotrophomonas using amplified ribosomal DNA restriction analysis followed by their respective 16S rDNA sequence analyses with that of the data available in NCBI GenBank. All four isolates showed tolerance to NaCl ranging from 1.37 to 2.57 mol/L in the nutrient agar medium. Under a 200 mmol/L salt stress in vitro, the bacteria in a culture of 108 CFU/ml exhibited competitive exopolysaccharide (EPS) production: Stenotrophomonas (65 µg/ml) and Bacillus (28 µg/ml), when compared to a positive control, Pseudomonas spp (23.65 µg/ml), a phenomenon ably supported by their strong biofilm-producing abilities both in a microtiter plate assay and in soil condition; and demonstrated by images of the scanning electron microscope (SEM). Overall, the isolated endophytic microorganisms revealed potential PGP activities that could be supported by their biofilm-forming ability under salinity stress, thereby building up a sustainable solution for ensuring food security in coastal agriculture under changing climate conditions.